Word Formation Process on Kaskus - Florencia, Shalliny (LANTERN (Journal on English Language, Culture and Literature), 2016)
This research shows that there are word formation processes on Kaskusfor communications. The background of the research is that there are a lot of people who are confused when they visit Kaskusfor the first timebecause of the new words formed by the kaskusers. The purpose of this research is to describe the word formation processes that happen on Kaskus, so that the non-kaskuserswho visit Kaskus will have knowledge about the words the kaskusers talk about. Thetheoretical framework used in this research concerns word formation process as is proposed by some experts like O’Grady (1996), Katamba (1993), and Hatch and Brown (1995). This research is descriptive research and it uses qualitative approach. The data in this research are posts in 2015 and taken directly from Kaskus using documentation, observation and interview method. The writer also uses note-taking and SimakBebasLibatCakap(SBLC) technique to support the methods used in the research. The result of the research shows that there are some word formation processes used on Kaskus by kaskusers, such as reduplication,back formation, clipping, blending, compounding, derivation, borrowing, coinage, initialization, and conversion, and initialization process is quite productive among other processes found on Kaskus.